Static Validation of Dynamically Generated HTML - Brabrand, Claus; Møller, Anders; Schwartzbach, Michael I. (BRICS Report Series, 2001)
We describe a static analysis of <bigwig> programs that efficiently decides if all dynamically computed XHTML documents presented to the client will validate according to the official DTD. We employ two interprocedural flow analyses to construct a graph summarizing the possible documents. This graph is subsequently analyzed to determine validity of those documents.